The Post-Islamist Turn: Reconciling Maqasid al-Shariah with Global Ethical Standards in Finance - Iqbal Faza (Lembaga penelitian dan pengabdian kepada masyrakat, 2026)
The global Islamic finance industry has undergone substantial transformation, increasingly oriented toward social inclusion, environmental sustainability, and universal ethical standards—a shift theoretically framed through the lens of post-Islamism. While existing scholarship on Islamic finance has predominantly focused on the technical dimension of Shariah compliance—product structures, contractual validity, and regulatory standards—this article addresses a critical gap: the ideological and sociological drivers of the industry’s strategic reorientation have remained largely underexplored, leaving scholars without a coherent framework to explain why Islamic financial institutions are increasingly adopting ESG principles, issuing green sukuk, and pursuing universal ethical standards beyond the confessional boundaries of their original mandate. This article examines how post-Islamist dynamics reshape strategy, product innovation, and governance within Islamic financial institutions. Employing a qualitative approach and systematic content analysis of academic literature, regulatory documents, annual reports, and industry publications, the study identifies three principal axes of transformation: (1) the expansion of financial inclusion through Islamic fintech and microfinance instruments targeting underserved populations, particularly micro, small, and medium enterprises (MSMEs); (2) the adoption of sustainability commitments embodied in the issuance of green sukuk and the integration of Environmental, Social, and Governance (ESG) principles; and (3) the articulation of a global ethical framework grounded in Shariah values of justice (ʿadl), transparency, and corporate social responsibility (CSR). Evidence drawn from the Indonesian case—the world’s largest Muslim-majority nation and a regional leader in Islamic finance—demonstrates that post-Islamist orientation enables Islamic financial institutions to transcend confessional boundaries, attract broader investor bases, and align with international development agendas, including the United Nations Sustainable Development Goals (SDGs). Theoretically, the paper advances the discourse on the intersection of Islamic political thought and financial economics, arguing that post-Islamism functions not as a departure from Shariah but as a hermeneutical renewal that renders Islamic finance globally competitive and socially transformative. The findings have implications for policymakers, regulators, and Islamic financial practitioners seeking to balance religious normativity with contemporary market demands